Filtração em campo ultrassônico - Rocha, Inaura Carolina Carneiro da (2009)
Filtration under ultrasonic condition is a technique that is gaining importance in wastewater treatment field. The main objective of this research was the study ultrasonic waves influence on the filtration of solid-liquid systems, in order to increase the operation performance and the regenerative capacity of the filter medium. A porous ceramic filter, whose filtration area was about 0.016 m2, was applied to the filtration of produced water by three mechanisms: conventional, tangential and ultrasonic. Experiments were carried out with synthetic and real produced water from the fields of Carmópolis and Siririzinho in Sergipe - Brazil. The analyzed variables were oil and grease content (O&G) and total suspended solid (TSS) for each filtration mechanism. It was also analyzed the regeneration of the filter medium by applying backwashing with distilled water. The results showed a stabilization of permeate flow in the filtration assisted by ultrasound and higher regenerative capacity, even in conditions of TSS and O&G maxima. The permeate showed high quality in terms of O&G and suspended solids removal.